Assessment of patient satisfaction of services in primary healthcare centers of Shivamogga: a cross-sectional study - B., Ajay Mallya; N., Praveen Kumar; H., Sridevi N. (International Journal Of Community Medicine And Public Health, 2021)
Background: India is the second most populous country in the world. Studies have shown that quality of primary health care in low to middle income countries is very poor. Patient’s perception of quality of health care service provided has strong relation with the utilization the services. Hence it’s important to monitor the health care delivery systems in the country to gain more knowledge about the health care delivery systems. Methods: A cross-sectional study was conducted in selected primary healthcare centres (PHCs) in Shimoga. 5 PHCs were selected by simple random sampling. 30 patients attending the facility were randomly chosen for exit interview. Data regarding patient’s perception of quality of health care provided by the facility was collected using a questionnaire. Results: Majority of the participants (68%) found the services provided by the facility to be satisfactory. Patients showed high satisfaction towards explanation provided the regarding problem by doctor (84%) and cleanliness of the facility (87.3%). Poor satisfaction was seen towards availability of medicines (54%) and behaviour of the paramedical staff (46%). Conclusions: There is a need to improve the quality of services provided by the primary healthcare centres to achieve better patient satisfaction and utilization.